Multi‐Step and Switchable Energy Transfer in Photoluminescent Organosilicone Capsules - Longyue Yu; Hailong Liu; Ning Feng; Gang Yi; Xia Xin; Jingcheng Hao; Hongguang Li (Advanced Science, 2024)
Abstract Light‐harvesting is of vital importance for many events, such as photosynthesis. To efficiently gather and transfer solar energy, delicate antenna is needed, which has been achieved by algae and plants. However, construction of efficient light‐harvesting systems using multiple, artificial building blocks is still challenging. Here, blue‐emitting organosilicone capsules containing carbon dots (denoted as CDs‐Si) in ethanol are prepared, which can effectively transfer energy to green‐emitting (silicone‐functionalized bodipy, Si‐BODIPY) or red‐emitting (rhodamine b, RhB) dyes. In ternary system, sequential Förster resonance energy transfer from CDs‐Si to Si‐BODIPY and further to RhB is realized, which is accompanied with a less pronounced, parallel FRET directly from CDs‐Si to RhB. The overall efficiency of energy transfer reaches ≈86%. By introducing a photoswitch (1,2‐bis(2,4‐dimethyl‐5‐phenyl‐3‐thienyl)‐3,3,4,4,5,5‐hexafluoro‐1‐cyclopentene, DAE) to the system, the emission becomes switchable under alternative illumination with UV and visible light, leading to the formation of smart artificial light‐harvesting systems.